Viral Justice and Public Pressure: An Analysis of the Role of Social Media in Handling Cases of Sexual Violence in Indonesia - Henny Saida Flora (Pt. Anagata Sembagi Education, 2026)
Sexual violence remains a persistent and under-prosecuted crime in Indonesia, where survivors frequently encounter institutional inertia, evidentiary hurdles, and social stigma that stall formal legal processes. Over the past five years, social media platforms have emerged as an alternative arena in which survivors, activists, and the wider public expose stalled cases, mobilize sympathy, and generate what scholars term